Internalization Of Humanistic Values In The Learning Process For The Millennial Generation - Nurlaelah Nurlaelah (Publikasi Indonesia, 2023)
In this era of globalization, Science and Technology (S&T) have become incredibly popular in daily life. S&T has brought people closer together and made the world more transparent. This situation poses a dilemma stemming from the remarkable progress of S&T. On one hand, this progress has made life more convenient for humans. On the other hand, our conscience raises concerns as we find ourselves in a situation that is no longer human-centric but rather technocentric. The millennial generation, born between the 1980s and the 2000s, is deeply intertwined with technological advancements, hence the term